Ecotheology Based Religious Moderation: A Study of Indonesia’s Interfaith Rainforest Initiative (IRI) - Melinda Nur Ekawati; Maemonah Maemonah; Durotul Qoyimah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
The contemporary global ecological crisis reflects not only environmental degradation but also a spiritual and epistemological rupture that has desacralized nature. This study aims to analyze the integration of Seyyed Hossein Nasr’s ecotheological thought with the values of religious moderation in the interfaith movement of the Interfaith Rainforest Initiative (IRI) Indonesia. Employing a qualitative approach with document based thematic analysis, this study examines official reports, policy statements, and institutional publications of IRI Indonesia. The analytical framework is constructed from Nasr’s core concepts tawhid, amanah, khalifah fi al-ard, mizan, critique of the desacralization of nature, and sacred science integrated with the principles of religious moderation promoted by the Indonesian Ministry of Religious Affairs. The findings indicate that IRI Indonesia consistently frames forests as a sacred trust and operationalizes this notion through interfaith collaboration in education, advocacy, and science-informed conservation practices. Although the integration of science and religion within IRI remains predominantly ethical and pragmatic rather than fully ontological as envisioned by Nasr, this approach has proven effective in building moral legitimacy, strengthening interfaith solidarity, and enhancing public participation in forest conservation. This study concludes that the synthesis of Nasr’s ecotheology and religious moderation offers a viable operational paradigm for faith-based environmental movements in plural societies.